Identifikasi Pengukuran Kinerja Keuangan Berdasarkan Value Added Intellectual Coefisient (Vaictm) Pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia (BEI) - Santy Mayda Batubara (JURNAL MANAJEMEN MOTIVASI, 2016)
The existence of a large difference between the market value and the reported values would make the financial statements are useless for decision making for investors who will invest in the company. The purpose of this study is as a source of information for investors to conduct analysis and investment decisions in the stock market, especially manufacturing companies listed in Indonesia Stock Exchange. The design of this research is done using secondary data and purposive sampling techniques, the overall manufacturing company in the consumer goods industry sector, listed on the Stock Exchange, from 2011 up to 2014. The research model using multiple linear regression, which was conducted to determine the effect of free variables, Value Added Intellectual Coeffisient (VAIC TM), consisting of: VACA (X1), VAHU (X2), STVA (X3) on the dependent variable is financial performance, which consists of: Ratio on Assets (ROA) (Y1) and Market Value (Y2). The conclusion of this study are: (1) simultaneously (test F), Value Added Intellectual Coefisient (VAICTM) effect on financial performance consisting of ratios Return on Assets (ROA) is 15.078> 2.69; 0.000 <0.05 and Market Value, is 12.047> 2.69; 0.000 <0.05; (2) partially (t test), Value Added Intellectual Coefisient (VAICTM) effect on the financial performance, the ROA is Physical Capital and Structural Capital, namely 0.000 <0.05, and the Market Value of variables, namely Structural Capital course , namely 0.000 <0.05, and 3) in the coefficient of determination R Square or the amount of Value Added Intellectual Coefisient (VAICTM) has a fairly close relationship to the Financial performance Ratio for the variable on Assets (ROA), is 0.558 and Market Value, is 0.515 Keywords: Physical Capital, Human Capital, Structural Capital Ratio on Assets and Market Value